Integrasi Media Pembelajaran pada Kurikulum Merdeka Belajar di Lingkungan Siswa SMK - Bayu Retno; Cundra Bahar; Brasie Pradana Sela Bunga Riska Ayu; Joni Wilson Sitopu; Ade Taufan; Mas’ud Muhammadiah (Journal on Education, 2023)
The formation of a new curriculum certainly has its drawbacks. The shortcomings of this independent learning curriculum are that it is an obstacle and a hand for the independent learning curriculum. There are several obstacles or challenges that must be faced. This study aims to obtain the results of heritage analysis regarding the integration of learning media in the independent learning curriculum in vocational students. The method used is a literature review. Of the three keywords that became the focus of the discussion, 145 related articles were found. Of the 145 that have been obtained, another filtering is carried out to see whether the articles of the three variables are related to each other or not. Based on these provisions, 20 articles were found. 20 is what is used as a review study in writing this article. The results of the review that have been carried out are that the Independent Learning Curriculum has four programs. The programs are (1) USBN replaced with an assessment (assessment), (2) 2021 UN replacement, (3) shortened RPP, (4) more flexible PPDB zoning. This program provides opportunities for schools, students, teachers, etc. to develop the learning process. Learning media can be one way to realize the success of this program is by integrating learning media based on technology and computer information